2016
DOI: 10.1007/s00710-016-0452-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of trace-element zoning in fluorapatite using BSE and CL imaging, and EPMA and μPIXE/μPIGE mapping

Abstract: In this paper, zonation patterns of trace elements in fluorapatite are discussed that were visualized using four analytical techniques, namely back-scattered electrons (BSE) and cathodoluminescence (CL) imaging, electron probe micro-analysis (EPMA), and micro-proton-induced X-ray/ gamma ray emission (μPIXE/μPIGE) mapping. Each method demonstrates the in-grain compositional variations in a slightly different way. Both BSE and CL provide qualitative data, and the internal textures are displayed in most detail. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The sharp peaks at ca. 600 and 630 nm most likely correspond to Sm 3þ , and the wide peak at 450 nm corresponds to Ce 3þ (Waychunas 2002, Gros et al 2016. Abbreviations: pAp -primary fluorapatite; sAp -secondary fluorapatite; rp -REE-phase.…”
Section: Fig 3 (A B) Cathodoluminescence Rgb Composite Imagesmentioning
confidence: 99%
“…The sharp peaks at ca. 600 and 630 nm most likely correspond to Sm 3þ , and the wide peak at 450 nm corresponds to Ce 3þ (Waychunas 2002, Gros et al 2016. Abbreviations: pAp -primary fluorapatite; sAp -secondary fluorapatite; rp -REE-phase.…”
Section: Fig 3 (A B) Cathodoluminescence Rgb Composite Imagesmentioning
confidence: 99%
“…Scales in counts per second (×10 3 ). Measured isotopes: 118 Sn, 182 W, 27 Al, 89 Y, 75 As, 56 Fe, 238 U, 47 Ti, 90 Zr, 45 Sc, 51 V, 140 Ce, 146 Nd, 93 Nb, 165 Ho, 175 Lu, 178 Hf.…”
Section: Statistical Treatment Of La-icp-ms Datamentioning
confidence: 99%
“…This may be investigated by integrated use of LA-ICP-MS and EBSD studies. Although not using LA-ICP-MS, the multi-technique study of trace-element zoning in fluorapatite using BSE and CL imaging, and EPMA and µPIXE/µPIGE mapping [165] is exemplary of the kind of approach destined to become more common in the future.…”
Section: Current Trends and Future Opportunitiesmentioning
confidence: 99%
“…Gros et al . () also showed the utility of combining several complementary methods. Here, electron‐based techniques (EPMA, BSE imaging and cathodoluminescence) were combined with accelerator‐based micro‐PIXE and micro‐PIGE to visualise the zonation patterns of trace elements in fluoroapatites.…”
Section: Advances In Accelerator‐based Methodsmentioning
confidence: 95%
“…EPMA generally has better spatial resolution but for a limited number of elements, while PIXE maps have a lower spatial resolution but include a larger number of elements at lower detection limits. Gros et al (2016) also showed the utility of combining several complementary methods. Here, electron-based techniques (EPMA, BSE imaging and cathodoluminescence) were combined with accelerator-based micro-PIXE and micro-PIGE to visualise the zonation patterns of trace elements in fluoroapatites.…”
Section: Examples Demonstrating the Capabilities Of Iba Techniques Inmentioning
confidence: 98%